2022
DOI: 10.3934/qfe.2022024
|View full text |Cite
|
Sign up to set email alerts
|

Staggered loans: A flexible modality of long-term financing for SMEs in global health emergencies

Abstract: <abstract> <p>Context: The context of this paper is the unprecedented global situation which has been and is still experiencing all countries all over the world, due to the pandemic caused by Covid-19 and its variants. Apart from the important problem of health population, all countries are facing a sharp reduction in their main economic indicators: stock indices, GDP (Gross Domestic Product), rates of employment, closing down of businesses, etc. Results: In this paper, we have presented and mathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For small and medium-sized enterprises (SMEs), governmental assistance proved instrumental in shaping their reopening strategies (Ludvig, 2021). Rambaud et al (2022) posited that staggered loans could serve as financial lifebuoys for struggling SMEs, while Tang et al (2021) found that entrepreneurs with high alertness were less inclined to resume operations.…”
mentioning
confidence: 99%
“…For small and medium-sized enterprises (SMEs), governmental assistance proved instrumental in shaping their reopening strategies (Ludvig, 2021). Rambaud et al (2022) posited that staggered loans could serve as financial lifebuoys for struggling SMEs, while Tang et al (2021) found that entrepreneurs with high alertness were less inclined to resume operations.…”
mentioning
confidence: 99%